Mobility-as-a-service for improving mobility in smart cities – a comparative analysis of selected cities - Koźlak, Aleksandra; Pawłowska, Barbara (Mobility-as-a-Service jako rozwiązanie usprawniające mobilność w inteligentnych miastach – analiza porównawcza wybranych miast, 2019)
The smart city concept has been growing in importance in the research activities worldwide as a direction in the development of modern cities. Mobility-as-a-Service (MaaS) solutions are quite a new transport concept introduced in a small number of cities usually in the pilot phase. The main purpose of the article is to explore the interactions and complementarity of these concepts. This paper analyses how MaaS can support progress in achieving smart mobility, and thus the idea of a smart city. It has the potential to improve the use of assets and contributes to a reduction in the number of passenger cars in congested cities. The research methodology includes a literature review and a deductive research method. The research has shown that cities having high indexes of ‘smartness’ are more likely to implement technologically advanced ICT solutions in transport systems and both these concepts (smart city and Mobility-as-a-Service) are important for the future of cities making them more sustainable and providing a higher quality of life for residents and visitors. The results of this study can be useful for policy makers, especially at local and regional levels
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 10, s. 31-46